Ancient Carved Ambers in the J. Paul Getty Museum - Faya Causey (Getty Publications, 2020)
First published in 2012, this catalogue presents fifty-six Etruscan, Greek, and Italic carved ambers from the Getty Museum's collectionthe second largest body of this material in the United States and one of the most important in the world. The ambers date from about 650 to 300 BC. The catalogue offers full description of the pieces, including typology, style, chronology, condition, and iconography. Each piece is illustrated.